2008
DOI: 10.1093/eurheartj/ehn216
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary infusion of autologous mononuclear cells from bone marrow or granulocyte colony-stimulating factor-mobilized apheresis product may not improve remodelling, contractile function, perfusion, or infarct size in a swine model of large myocardial infarction

Abstract: Intracoronary infusion of mononuclear cells from either BM or G-CSF-mobilized apheresis product may not improve or limit deterioration in systolic function, adverse ventricular remodelling, infarct size, or perfusion in a swine model of large MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…To distinguish autocrine versus paracrine effects of infused cells, we used robust molecular labeling strategies in combination with dual photon laser microscopy of the infarct core and border zones. We did not detect engrafted or transdifferentiated MSCs 6 weeks after injection in the IRA, consistent with recent reports from several laboratories that have suggested indirect vasculogenic effects or stimulatory effects on endogenous resident stem cells (17)(18)(19). Loss of plasticity of infused allogeneic MSCs after lentiviral infection or multiple in vitro passages or impaired growth factor synthesis capacity is unlikely, as evidenced in osteogenic and adipogenic differentiation assays and secretome analysis.…”
Section: Discussionsupporting
confidence: 91%
“…To distinguish autocrine versus paracrine effects of infused cells, we used robust molecular labeling strategies in combination with dual photon laser microscopy of the infarct core and border zones. We did not detect engrafted or transdifferentiated MSCs 6 weeks after injection in the IRA, consistent with recent reports from several laboratories that have suggested indirect vasculogenic effects or stimulatory effects on endogenous resident stem cells (17)(18)(19). Loss of plasticity of infused allogeneic MSCs after lentiviral infection or multiple in vitro passages or impaired growth factor synthesis capacity is unlikely, as evidenced in osteogenic and adipogenic differentiation assays and secretome analysis.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, Werneck-de-Castro et al [13] demonstrated that the administration of high doses of G-CSF early after MI failed to improve cardiac function at rest or under exercise stress in rats. Similar negative results were observed in mice [14], rats [15], porcine [16] and baboons [17]. Surprisingly, G-CSF administration resulted in LV enlargement and enhanced myocardial fibrosis [15].…”
Section: Introductionsupporting
confidence: 70%
“…Longer follow-up was not possible as these swine become too large for MRI. Although the sample size is small compared to human efficacy trials, it is comparable to other published large animal translational studies [27, 33, 49, 50]. Our study exploited highly sensitive and reproducible endpoints such as quantitative cardiac MRI, invasive pressure-volume hemodynamics, implanted VT monitoring, and systematic histopathology to compensate for the small sample size.…”
Section: Discussionmentioning
confidence: 76%
“…Closed chest antero-septal MI was induced in 36 female Yorkshire swine weighing 30 kg using methods previously described by our group [26, 27]. Briefly, animals were sedated with an intramuscular injection of Telazol 4–6 mg/kg and Xylazine 2 mg/kg and then intubated and mechanically ventilated with1–3 % isoflurane.…”
Section: Methodsmentioning
confidence: 99%